PENYIMPANGAN DI TEMPAT KERJA: ANTESEDEN DAN KONSEKUENSI - Danang Sunyoto; M.A. Kalijaga (JOEL: Journal of Educational and Language Research, 2022)
Purpose – This study aims to determine the role of self-monitoring, self-control, and self-regulatory on deviations in the workplace and work performance. Design / Methodology / Approach – The sample of this research is 120 company operational workers with various levels of position and work status. Methods of collecting and analyzing data with questionnaires and quantitative. Result-Self-monitoring, self-control, and self-regulation negatively contribute to workplace deviance; self-monitoring has a positive role and self-control, self-regulatory does not play a role, and deviations at work have a negative role on work performance; deviation at work is not a mediator of the role of self-monitoring on work performance, but as a mediator of the positive role of self-control and self-regulatory on job performance. Originality – Religious values ​​still need to be researched. This research offers the use of sociological theory approach, psychological theory, social sociology theory to discuss the research results.